Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan PT Compotec International Bogor - Martin Krisna Priyatno; Lingga Yuliana (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
This study was conducted on employees of PT. Compotec International Bogor. This study aims to analyze and determine the influence of the work environment and work motivation on the job satisfaction of employees of PT. Compotec International Bogor. The research method used is a qualitative approach by collecting information through interviews with 2 people, who are employees of PT. Compotec International Bogor, and other information through articles that are in accordance with what is being studied, as well as from its official website. Based on the results of the study, it was found that the work environment and motivation affect job satisfaction. A comfortable and safe work environment, as well as coworkers who encourage each other will have an impact on work. If the work environment is uncomfortable or there is no motivation, it will affect work, work will be difficult.